Co-Activating Lattice Oxygen of TiO2-NT and SnO2 Nanoparticles on Superhydrophilic Graphite Felt for Boosting Electrocatalytic Oxidation of Glyphosate - Wenyan He; Sheng Bai; Kaijie Ye; Siyan Xu; Yinuo Dan; Moli Chen; Kuo Fang (Nanomaterials)
Glyphosate (GH) wastewater potentially poses hazards to human health and the aquatic environment, due to its persistence and toxicity. A highly superhydrophilic and stable graphite felt (GF)/polydopamine (PDA)/titanium dioxide nanotubes (TiO2-NT)/SnO2/Ru anode was fabricated and characterized for the degradation of glyphosate wastewater. Compared to control anodes, the GF/PDA/TiO2-NT/SnO2/Ru anode exhibited the highest removal efficiency (near to 100%) and a yield of phosphate ions of 76.51%, with the lowest energy consumption (0.088 Wh/L) for degrading 0.59 mM glyphosate (GH) at 7 mA/cm2 in 30 min. The exceptional activity of the anode may be attributed to the co-activation of lattice oxygen in TiO2-NT and SnO2 by coupled Ru, resulting in a significant amount of •O2− and oxygen vacancies as active sites for glyphosate degradation. After electrolysis, small molecular acids and inorganic ions were obtained, with hydroxylation and dephosphorization as the main degradation pathways. Eight cycles of experiments confirmed that Ru doping prominently enhanced the stability of the GF/PDA/TiO2-NT/SnO2/Ru anode due to its high oxygenophilicity and electron-rich ability, which promoted the generation and utilization efficiency of active free radicals and defects-associated oxygen. Therefore, this study introduces an effective strategy for efficiently co-activating lattice oxygen in SnO2 and TiO2-NT on graphite felt to eliminate persistent organophosphorus pesticides.